PERAN PEGADAIAN DALAM USAHA PEMBERDAYAAN MASYARAKAT (STUDI KASUS TENTANG PRODUK KRISTA & USAHA RUMAH TANGGA PADA NASABAH KRISTA PT PEGADAIAN CABANG PEKANBARU KOTA) - Ramadhanes "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Company Limited (PT) Pegadaian as one of the State-Owned Enterprises (SOEs) participate and help improve the welfare of the community, especially the middle class down by means of distributing a wide range of credit facilities are fast, easy and secure, One of the credit facility is Business Credit Household (Krista). The purpose of this study was to determine how the role of PT. Pegadaian in community development efforts. Data collection method used is the field of research and literature study with quantitative descriptive analysis of the data using figures and tables and described systematically.Business Credit Household (Krista) is one of the credit facilities granted to small and medium entrepreneurs preferred women. The prerequisite is a small entrepreneur / medium, identity cards and family cards, become a member of a group of business has been running for at least 6 months, and currently has no debt. The procedure to be followed by prospective borrowers very fast, easy and secure. Which include prospective borrower fills the credit request form (FPK), further functional Krista will conduct a survey and analysis of credit. If decent credit is given, then the prospective customer will perform a credit agreement with Pegadaian engagement. The last process is the disbursement of credit through the checkout.Keywords: Role of Pegadaian, Business Empowerment